Cartilage loss in radiographically normal knees depends on radiographic status of the contralateral knee – data from the Osteoarthritis Initiative. Issue 2 (February 2019) - Eckstein, F.; Maschek, S.; Roemer, F.W.; Duda, G.N.; Sharma, L.; Wirth, W.
Summary: Objective: To test whether radiographically normal knees with contralateral radiographic knee osteoarthritis (OA), but without contralateral trauma history, display greater cartilage thickness loss than knees from subjects with bilaterally radiographically normal knees. Methods: 828 radiographically normal knees (Kellgren Lawrence grade [KLG] 0) from the Osteoarthritis Initiative [OAI] were studied; 150 case knees displayed definite radiographic knee OA (KLG ≥ 2) contralaterally, and had MRI double echo steady state (DESS) images available at 12 and 48 month follow-up. 678 reference knees displayed KLG0 at the contralateral side. Cartilage thickness change was determined in femorotibial subregions and location-independent cartilage thinning scores were computed. Case and reference knees were compared using ANCOVA. Results: Of the 150 KLG0 case knees, 108 had a contralateral KLG2 knee (50 without, and 58 with joint space narrowing [JSN]), 31 a KLG3 and 11 a KLG4 knee. The cartilage thinning score tended to be greater in case than reference knees; the cartilage thinning score in KLG0 case knees with contralateral radiographic JSN (−858 μm; [95% confidence interval −1016, −701 μm]) was significantly greater ( P = 0.0012) than that in bilaterally KLG0 reference knees (−634 μm; [−673, −596 μm]), whereas KLG0 knees with contralateral KLG2 without JSN only showed relatively small thinning scores (−530 μm, [−631, −428 μm]). Region-specific analysis suggested greater rates of cartilage loss in case than in reference knees in the lateral, rather than medial, femorotibial compartment. Conclusions: Radiographically normal knees with contralateral JSN may serve as a human model of early OA, for testing disease modifying drugs in clinical trials designed to prevent cartilage loss before the onset of radiographic change. Clinicaltrials.gov identification: NCT00080171 .